Minocycline treatment inhibits microglial activation and alters spinal levels of endocannabinoids in a rat model of neuropathic pain - Elphick Maurice R; Barrett David; Eldeeb Khalil; Jhaveri Maulik; Richardson Denise; Guasti Leonardo; Alexander Stephen PH; Kendall David; Michael Gregory J; Chapman Victoria (SAGE Publishing, 2009)
Abstract Activation of spinal microglia contributes to aberrant pain responses associated with neuropathic pain states. Endocannabinoids (ECs) are present in the spinal cord, and inhibit nociceptive processing; levels of ECs may be altered by microglia which modulate the turnover of endocannabinoids in vitro. Here, we investigate the effect of minocycline, an inhibitor of activated microglia, on levels of the endocannabinoids anandamide and 2-arachidonoylglycerol (2-AG), and the related compound N-palmitoylethanolamine (PEA), in neuropathic spinal cord. Selective spinal nerve ligation (SNL) in rats resulted in mechanical allodynia and the presence of activated microglia in the ipsilateral spinal cord. Chronic daily treatment with minocycline (30 mg/kg, ip for 14 days) significantly reduced the development of mechanical allodynia at days 5, 10 and 14 post-SNL surgery, compared to vehicle-treated SNL rats (P < 0.001). Minocycline treatment also significantly attenuated OX-42 immunoreactivity, a marker of activated microglia, in the ipsilateral (P < 0.001) and contralateral (P < 0.01) spinal cord of SNL rats, compared to vehicle controls. Minocycline treatment significantly (P < 0.01) decreased levels of 2-AG and significantly (P < 0.01) increased levels of PEA in the ipsilateral spinal cord of SNL rats, compared to the contralateral spinal cord. Thus, activation of microglia affects spinal levels of endocannabinoids and related compounds in neuropathic pain states.